The public doesn't understand: The self-reinforcing interplay of image discrepancies and political ideologies in law enforcement - Patil, Shefali V. (Administrative Science Quarterly)
Drawing on information processing theory, I revisit prior assumptions that not being understood raises challenges for employees, examining how political ideologies powerfully affect how employees who serve the public react to a perceived lack of understanding of the difficulties of their jobs. Using independent expert ratings of 794 body camera videos of 164 police officers across two agencies, I show that a lack of perceived public understanding decreases task performance for liberal-leaning officers but not for conservative-leaning officers. Because liberal-leaning officers seek to form more communal relationships with the public, a perceived lack of public understanding violates their sense of social order, but it merely reaffirms conservative-leaning officers$1 (Bbeliefs in maintaining an authoritarian distance given the responsibilities and duties they shoulder. I replicate these results using supervisors$1 (Bratings of 82 officers across four agencies and then demonstrate in a time-lagged survey of 184 officers in a single agency that those with stronger conservative beliefs are more likely to believe the public fails to appreciate the difficulties of their jobs. These studies highlight the importance of accounting for people$1 (Bs beliefs in whether image conflicts should and do arise$1 (Band provide insights into the self-reinforcing forces that sustain divides between employees and those they serve. - Reproduced.s